International business - Czinkota, Michael R., 1951-; Ronkainen, Ilkka A.; Gupta, Suraksha (Cambridge : Cambridge University Press, 2021)
Thoroughly updated, the 9th edition of this bestselling textbook incorporates global trends and data, supported by an exemplary case selection based on firms from around the world. The internationally cited author team of Czinkota, Ronkainen, and Gupta balance conceptual understanding of business theory with the day-to-day realities of business practice, preparing students to become successful participants in the global business place. This edition brings greater focus on Asia and emerging markets, as well as Brexit, the impact of COVID-19 on business and the importance of technology and the digital space to international business practice. Through its discussion and analysis, the book guides students to a greater understanding of contemporary business issues and helps them to develop new tools of analysis. Covering all key aspects of international business, the authors emphasize a few key dimensions: international context, role of government in international business, small- and medium-sized firms, and social responsibility.
Title from publisher's bibliographic system (viewed on 26 Aug 2021).
Keywords: elektronické knihy; electronic books; International trade; International business enterprises -- Management; International business enterprises; Investments, Foreign; International finance